2019
DOI: 10.1002/capr.12261
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on Maltese school‐based counselling practices: An autoethnographic collaborative writing project

Abstract: Maltese counsellors working in schools are, at times, just making ends meet due to lack of human resources and work schedules. ‘Why do our students/children have to repeat the same story to so many professionals?’ teachers/parents angrily query. This autoethnographic study voices our professional experiences as authors and participants. This empowers us to be advocates for our young clients. Collaborative autoethnography (CAE) methodology best fits our research question as we ‘seek to discover and systemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Possibly the counsellor/entertainer could evade burnout through hobbies (e.g., Grosch & Olsen, 1995; Karakoc et al., 2016; Stearns & Moore, 1993), and thus, self‐care should be considered. Bond (2010) stressed that counsellors are ethically obliged to practise self‐care and avoid burnout, mainly caused when professional helpers invest a lot emotionally in others, without caring properly for themselves (e.g., Everall & Paulson, 2004; Falzon et al, 2019; Rosenberg & Pace, 2007). Kennedy and Charles (2001) concluded that professional helpers’ wellbeing is more affected than other professionals, as therapists are emotionally invested in their clients.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly the counsellor/entertainer could evade burnout through hobbies (e.g., Grosch & Olsen, 1995; Karakoc et al., 2016; Stearns & Moore, 1993), and thus, self‐care should be considered. Bond (2010) stressed that counsellors are ethically obliged to practise self‐care and avoid burnout, mainly caused when professional helpers invest a lot emotionally in others, without caring properly for themselves (e.g., Everall & Paulson, 2004; Falzon et al, 2019; Rosenberg & Pace, 2007). Kennedy and Charles (2001) concluded that professional helpers’ wellbeing is more affected than other professionals, as therapists are emotionally invested in their clients.…”
Section: Introductionmentioning
confidence: 99%